MANAJEMEN PERSEDIAAN BAHAN BAKU KERIPIK PISANG DI INDUSTRI “FLAMBOYAN” KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Erikayanti, Agustin Dwi; Laapo, Alimuddin; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
This research aims to know the amount of the purchase of raw materials is the most economical and knowing the exact time of booking back in the industry "flamboyant" Village of the subdistrict Tawaeli the Palu City. Research locations selected intentionally (Purposive) on industry "flamboyant" which it produces banana chips with major raw material is banana horns. The respondent's determination was done deliberately (Purposive) by the number of respondents as much as 3 outsiders which consists of 1 and 2 employees. Methods of analysis used is the analysis of the inventory (Safety Stock, EOQ, ROP,). The results in this research showed that the number of economical raw material purchase banana chips should be done by the industry "flamboyant" in July 2015-June 2016 average of 756.08 Kg of seat Inventory 252 Kg. Reordering should be available in the warehouse as much as 630.04 Kg. The Total cost of the inventory budget issued industry “flamboyant” in July 2015-June 2016 an average of Rp 32,566.116.